IRX3 depletion promotes early cardiac commitment of hiPSC-Derived Cardiomyocytes - Agatha Ribeiro Kalthof; Nikolas Dresch Ferreira; Caio Mateus Silva; Iuri Cordeiro Valadão; Iguaracy Pinheiro de Sousa; Ester Riserio Matos Bertoldi; Vanessa Morais Lima; Lauro Thiago Turaca; Ana Beatriz Ruiz Afonso Barbosa; Miriam Helena Fonseca-Alaniz; Jean-Paul Concordet; Elida Adalgisa Neri; et al. (PLoS ONE, 2026)
Generating mature human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) remains a major obstacle to accurate disease modeling and cardiac repair. As the transcription factor Irx3 is a key determinant of ventricular conduction system fate in mice, we hypothesized that suppressing IRX3 expression accelerates human working cardiomyocyte differentiation. Here, we demonstrate that depleting IRX3 enhances hiPSC-CM differentiation. IRX3 -knockout (KO) hiPSCs generated a greater number of cardiomyocytes with elevated expression of TNNI1 and CX43. Notably, IRX3 -KO cardiomyocytes exhibited improved electrophysiological properties, more uniform mitochondrial distribution, better sarcomere organization, and enhanced intercellular connectivity. We observed that IRX3 expression peaks during the early stages of cardiomyocyte differentiation, whereas IRX3 -KO cardiac progenitors have increased expression of GATA4, NKX2–5, and TBX5 , as well as enhanced cell proliferation. These integrative analyses indicate that IRX3 influences cardiomyocyte differentiation by modulating the gene regulatory networks driven by GATA4, NKX2–5, and TBX5, providing functional evidence linking gene regulatory networks to the structural and electrophysiological development of cardiomyocytes. Collectively, these findings identify IRX3 as a key regulator of early cardiac commitment and highlight the potential of IRX3 suppression to enhance the molecular and functional phenotype of hiPSC-derived cardiomyocytes.